Level structure and spin-orbit effects in quasi-one-dimensional semiconductor nanostructures - Romano, Carla Lidia (2005)
We investigate theoretically how the spin-orbit Dresselhaus and Rashba effects influence the electronic structure of quasi-one-dimensional semiconductor quantum dots, similar to those that can be formed inside semiconductor nanorods. We calculate electronic energy levels, eigenfunctions, and effective g-factors for coupled, double dots made out of different materials, especially GaAs and InSb. We show that by choosing the form of the lateral confinement, the contributions of the Dresselhaus and Rashba terms can be tuned and suppressed, and we consider several possible cases of interest. We also study how, by varying the parameters of the double-well confinement in the longitudinal direction, the effective g-factor can be controlled to a large extent.